Using Geographic Information System (GIS) to estimate the volume of water for Al Dammam unconfined Aquifer within Al Salman basin, Al- Muthana Governorate, South West Iraq - Al-Sheikh, Osamah N.; Al-Shammaâ€™a, Ayser M. (Iraqi Journal of Science, 2019)
The groundwater represents the main source of water in the study area due to lack of surface water. The Dammam unconfined aquifer represents the main aquifer in the study area and Southern desert because of the regional extent, the quantity and quality of water. Many groundwater wells have been drilled in the study area to coverage the huge demand of water for agricultural purposes. The Geographic Information System (GIS) was used to estimate the volume of water which calculated (25.6964 Ã— 109 m3) within the study area , automate calculation of the area of Al Salman basin using digital elevation models, derive the thickness maps of AlDammam unconfined aquifer from Key holes (KH) and Bore holes (BH), draw the groundwater head and flow map in the study area. Such data derived from GIS can help authorities and researchers for groundwater management and further development within the study area.